Hubungan Pernikahan Dini dan Status Gizi dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Binanga Kabupaten Mamuju - Hajrah, Fifit; Parwati, Dewi; Rismaida, Martalina; Fadhilah, Iin; Nur, Armiyati (Mando Care Jurnal, 2025)
Anemia in pregnant women is a health problem that can increase the risk of pregnancy and childbirth complications. This study aims to analyze the relationship between early marriage and nutritional status with the incidence of anemia in pregnant women at the Binanga Health Center. The study used a cross-sectional design with a sample of 58 pregnant women selected by purposive sampling. Data were collected through interviews, measuring the upper arm circumference (MUAC), and examining hemoglobin levels, then analyzed using the Chi-square test and logistic regression. The results of this study show that early marriage and the nutritional status of pregnant women are significantly related to the incidence of anemia. Women who marry at a young age and have poor nutritional status are at a higher risk of experiencing anemia. Therefore, it is necessary to improve education about early marriage and ensure optimal nutrition before and during pregnancy. Intervention programs focusing on nutritional screening and anemia in adolescent girls and prospective brides are crucial to reduce the incidence of anemia in pregnant women and improve the health of both mothers and babies.